2011
DOI: 10.1007/s11069-010-9712-5
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorm Hazard vulnerability for the Atlanta, Georgia metropolitan region

Abstract: Most U.S. metropolitan regions have experienced urban ''sprawl,'' or the outward spreading of urban development from city centers. For cities lying in areas prone to severe weather, the sprawl phenomenon exposes greater numbers of developed areas and inhabitants to a variety of thunderstorm hazards. This study's principal goal is to determine how urbanization growth patterns affect a region's vulnerability to severe weather events. To assess how sprawl may impact vulnerability to tornadoes, hail, and convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…From 1950 to 2005, although nocturnal tornadoes comprised only 27% of total tornado activity, they accounted for about 40% of tornado fatalities (Ashley, Krmenec, & Schwantes, 2008) because they were less visible and occurred when most people were asleep. Tornadorelated fatalities associated with mobile homes were high because, in addition to the structural vulnerability of their dwellings, mobile home residents were less likely to seek shelter (Ashley, 2007;Chaney & Weaver, 2010;Paulikas & Ashley, 2011;Schmidlin, Hammer, Ono, & King, 2009;Schmidlin & King, 1995). Surveys and wind tunnel experiments have even suggested that staying in motor vehicles is less risky than remaining in mobile homes during tornadoes (Schmidlin et al, , 2009).…”
Section: Tornadoesmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1950 to 2005, although nocturnal tornadoes comprised only 27% of total tornado activity, they accounted for about 40% of tornado fatalities (Ashley, Krmenec, & Schwantes, 2008) because they were less visible and occurred when most people were asleep. Tornadorelated fatalities associated with mobile homes were high because, in addition to the structural vulnerability of their dwellings, mobile home residents were less likely to seek shelter (Ashley, 2007;Chaney & Weaver, 2010;Paulikas & Ashley, 2011;Schmidlin, Hammer, Ono, & King, 2009;Schmidlin & King, 1995). Surveys and wind tunnel experiments have even suggested that staying in motor vehicles is less risky than remaining in mobile homes during tornadoes (Schmidlin et al, , 2009).…”
Section: Tornadoesmentioning
confidence: 99%
“…Changnon (2009c) suggested that this increase in highly damaging hailstorms could be attributable to the expansion of the nation's urban areas, a suggestion that has been echoed by other authors. For example, Paulikas and Ashley (2011) found that dramatic increases in the size and density of the Atlanta metropolitan area from 1960 to 2006 had greatly increased the area's potential property losses in a hailstorm. Similarly, Changnon (2008e) suggested that the high ratio of hail property losses to hail events in the Midwest from 1949 to 2006 was due to the high density of property and wealth in that region.…”
Section: Hailmentioning
confidence: 99%
“…The methodology used by Paulikas and Ashley () consisted of subdividing 28 Atlanta MSA counties into 3 ‘ring’ sections (an Urban Core, Inner Ring and Outer Ring of counties), which revealed different rates of population growth found throughout the study region. The Urban Core of counties is comprised of the most historically developed counties in the Atlanta MSA with the highest population and housing unit density values (Paulikas and Ashley, ).…”
Section: Methodsmentioning
confidence: 99%
“…The methodology used by Paulikas and Ashley () consisted of subdividing 28 Atlanta MSA counties into 3 ‘ring’ sections (an Urban Core, Inner Ring and Outer Ring of counties), which revealed different rates of population growth found throughout the study region. The Urban Core of counties is comprised of the most historically developed counties in the Atlanta MSA with the highest population and housing unit density values (Paulikas and Ashley, ). The Inner Ring comprises counties lying immediately adjacent to the Urban Core which initially were very rural but have witnessed massive development since 1960 in areas to the north of the city limits (Paulikas and Ashley, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation